Dihydroquinolines, Dihydronaphthyridines and Quinolones by Domino Reactions of Morita-Baylis-Hillman Acetates - Joel K. Annor-Gyamfi; Ebenezer Ametsetor; Kevin Meraz; Richard A. Bunce (Molecules, 2021)
An efficient synthetic route to highly substituted dihydroquinolines and dihydronaphthyridines has been developed using a domino reaction of Morita-Baylis-Hillman (MBH) acetates with primary aliphatic and aromatic amines in DMF at 50–90 °C. The MBH substrates incorporate a side chain acetate positioned adjacent to an acrylate or acrylonitrile aza-Michael acceptor as well as an aromatic ring activated toward SNAr ring closure. A control experiment established that the initial reaction was an SN2′-type displacement of the side chain acetate by the amine to generate the alkene product with the added nitrogen nucleophile positioned trans to the SNAr aromatic ring acceptor. Thus, equilibration of the initial alkene geometry is required prior to cyclization. A further double bond migration was observed for several reactions targeting dihydronaphthyridines from substrates with a side chain acrylonitrile moiety. MBH acetates incorporating a 2,5-difluorophenyl moiety were found to have dual reactivity in these annulations. In the absence of O2, the expected dihydroquinolines were formed, while in the presence of O2, quinolones were produced. All of the products were isolated in good to excellent yields (72–93%). Numerous cases (42) are reported, and mechanisms are discussed.